2017
DOI: 10.4236/jbm.2017.53015
|View full text |Cite
|
Sign up to set email alerts
|

Nrf-2 and HO-1 Expression in Medulloblastoma: A Clinicopathological Analysis

Abstract: Medulloblastoma (MB) is one of the most common malignant tumors with poor survival in children. Nuclear factor erythroid 2-related factor2 (Nrf-2) and heme oxygenase-1 (HO-1) have been considered to play major roles in the pathogenesis of many tumors. There is no report about clinicopathological significance of Nrf-2 and HO-1 expression in medulloblastoma. In the present study, to explore the expression and potential function of Nrf-2 and HO-1 in MBs, immunohistochemistry was used to examine the Nrf-2 and HO-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In contrast to the significant amount of literature linking NRF2 with adult GBM, the current knowledge about its clinicopathological significance in MB is still poor. In a work from Tang et al, 2017 it has been demonstrated that NRF2 expression is enhanced in MB samples (n = 41) when compared to peritumoral control brain tissues (n = 27). Moreover, it was previously shown that pharmacological targeting of NRF2 with two NRF2-inducers (nifurtimox and tetrathiomolybdate) results in a synergic ROS-dependent antitumor response towards MB in vitro ( Koto et al, 2011 ).…”
Section: Metabolic Reprogramming In Medulloblastomamentioning
confidence: 99%
“…In contrast to the significant amount of literature linking NRF2 with adult GBM, the current knowledge about its clinicopathological significance in MB is still poor. In a work from Tang et al, 2017 it has been demonstrated that NRF2 expression is enhanced in MB samples (n = 41) when compared to peritumoral control brain tissues (n = 27). Moreover, it was previously shown that pharmacological targeting of NRF2 with two NRF2-inducers (nifurtimox and tetrathiomolybdate) results in a synergic ROS-dependent antitumor response towards MB in vitro ( Koto et al, 2011 ).…”
Section: Metabolic Reprogramming In Medulloblastomamentioning
confidence: 99%